The Correlation Between Teachers’ Friendly Attitude and Students’ Speaking Achievement - Nury Kurnia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The research aims at finding out the correlation between teachers’ friendly attitude and students’ speaking achievement. The sample of this research was class VIII A consist of 35 students of SMPT Madinatul Ulum Cangkring Kecamatan Jenggawah, Jember. The research was a correlational research which was attempting to find out the correlation between two variables, teachers’ friendly attitude and students’ speaking achievement. The statistical description of the two variables was conducted before calculating the score into Pearson product moment formula. Based on the data analysis, it was found that rxy0.677 was higher than r table 0.349 with significant level 0.05 or 5 % and df 33. Therefore, if rxy was higher than r table, it can be concluded that there was a positive correlation between teachers’ friendly attitude and students’ speaking achievement. The correlation indicated a high-strong correlation between the two variables. Keywords: correlation, teachers’ friendly attitude, students’ speaking achievement